Social Stratification of People with Mental Disorders in Islamic Boarding Schools - Hafid Syahrul Ramadhan; Ruth Bell; Supriyanto , Supriyanto; Md. Irteja Islam; Yakubu , Abubakar; Gökçekuyu , Ertuğrul (Journal of Social and Humanities, 2025)
Padepokan Tahfidzul Qur'an (PTQ) Ibnu Rusydi is famous for conducting a mental health healing process through an alternative route of memorizing the Qur'an. However, this raises a polemic because there are social classes that become obstacles in the rehabilitation of People with Mental Disorders (ODGJ). This study aims to determine the form of social stratification between old and new ODGJ students and the impact of social stratification between old and new ODGJ students at PTQ Ibnu Rusydi Jombang.  This type of research is descriptive qualitative research, with the research location at PTQ Ibnu Rusydi Jombang. Data collection techniques through interviews, observation and documentation. The informants used in this study were the caregiver, chairman, management, and santri of PTQ Ibnu Rusydi Jombang. Data analysis techniques using data reduction, data presentation and conclusion drawing. The findings of this study indicate that the social stratification of the Pondok Tahfidzul Qur'an Ibnu Rusydi includes the following; Social stratification of Abah Kiai on students as a function of Abah Kiai who is respected in terms of religious knowledge. The social stratification of the boarding house management as the responsibility given by Kiai to the boarding house management. Social stratification of old santri from a higher level of knowledge/experience with new santri. Social stratification of new students where their position of power is weak. The impact of social stratification includes reduced self-confidence when students get backgrounds of different races, education, economics, especially in terms of memorization that is not comparable to other students.